The Role of E-Commerce, Business Experience, and Industrial Agglomeration in Increasing the Income of Fashion SMEs in Denpasar - Ni Kadek Ria Pratiwi; Amrita Nugraheni Saraswaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprise (MSME) revenues are affected by various factors that determine business continuity and the welfare of their owners. This study aims to analyze, both simultaneously and partially, the effects of e-commerce usage, business experience, and industrial agglomeration on the revenues of fashion-sector MSMEs in Denpasar City. A total of 100 fashion MSME operators were sampled, and the data were analyzed via multiple linear regression using SPSS 26. The resulting coefficient of determination (R²) is 0.684, indicating that e-commerce usage (X₁), business experience (X₂), and industrial agglomeration (X₃) collectively explain 68.4% of the variance in MSME revenue (Y), with the remaining 31.6% attributable to factors beyond this study. The analysis shows that, together, the three independent variables significantly affect MSME revenues; separately, each—e-commerce usage, business experience, and industrial agglomeration—exerts a positive and significant impact on the revenues of fashion-sector MSMEs in Denpasar.